Collaboration as a Value in Islamic Education from Learning from Corpse Management - M. Nurul Humaidi; Ahmad Saefulloh; Romelah; Syafrul Nalus; Kadar Risman (Al-Hayat: Journal of Islamic Education, 2024)
This article examines collaboration as a core value in Islamic education, focusing on the partnership between two funeral organizations: the Muhammadiyah Branch Leadership Muslim Corpse Association (RKM PCM Palangkaraya) and the Shalahuddin Muslim Family Association (KKM Shalahuddin), which is affiliated with the University of Palangkaraya. The study utilizes a qualitative multi-case research approach to analyze the nature of cooperation, motivations, benefits, obstacles, and challenges in the kifayah process between the two families. Data collection methods included interviews with organizational administrators, observations of the kifayah process, and analysis of organizational charter documents and membership fees. The findings revealed a clear division of responsibilities: RKM PCM Palangkaraya oversees the rituals of washing and praying for the deceased, while KKM Shalahuddin provides equipment and coordinates the burial. This collaboration is vital for ensuring that the burial aligns with Islamic law, despite facing challenges such as communication barriers and funding limitations. The partnership enhances service delivery and nurtures mutual respect between the organizations. However, the lack of prior discussions regarding tahlil practices may create confusion about roles and responsibilities. The study underscores the importance of incorporating effective communication and mutual understanding into educational curricula, allowing students to grasp the values of cooperation and the principles of corpse management in Islam. This knowledge ultimately fosters character development and community skills, highlighting education's role in addressing societal needs within an Islamic framework. Future research is recommended to further investigate tahlil practices in this collaborative context to clarify the roles and responsibilities of each organization.